Paraoxonase activity in type 2 diabetes mellitus malay patients in Hospital Universiti Sains Malaysia (HUSM) - Ibrahim, Hanim Afzan (2015)
Introduction: Paraoxonase (PON) is an enzyme associated with high-density lipoprotein (HDL). PON is involved in the detoxification of lipid peroxides and play a role in decreasing oxidative stress which are related with the risk for complication in diabetes mellitus type 2(T2 DM) patients that is strongly associated with their diabetic control. The ability of PON to protect low density lipoprotein (LDL) against oxidation has been shown to vary between the three polymorphic forms (A, AB, B). PON with phenotype B is less efficient in protecting LDL against oxidation. Objectives: The purpose of this study was to determine the PON1 activities, PON1 phenotypic polymorphism, lipid profile and oxidized LDL (oxLDL) in T2 DM among Malay population and healthy control group, their relation with diabetic complications and the correlation between PON activities and lipid profile. Methods: A total of 99 subjects were chosen for three groups (healthy control, good control diabetes mellitus (HbA1c ≤ 6.5%) and poor control diabetes mellitus(HbA1c > 6.5%) (each group n=33). Fasting serum were analysed for PON, salt stimulated PON, arylesterase (AREase) activities, lipid profile and oxLDL. The phenotypes assesment for PON can be A, B, AB based on the ratio of salt stimulated PON to the AREase activity. Results: The basal PON and salt stimulated PON activities were not statistically significant among the three groups. AREase activity was lower in T2 DM patients compared to healthy control.Majority of subjects were AB phenotype and none of the healthy control subjects with B phenotype. Diabetic patients with chronic kidney disease (CKD) showed significantly lower salt stimulated PON activity when compared to those without CKD. Lipid profile analyses for poor control diabetic group showed significantly lower in total cholesterol (TC), HDL and LDL level and higher in triglyceride (TG) level compared to healthy control. A positive correlation between the HDL levels and basal PON activity in poor control diabetic and a positive correlation between the TC and HDL with salt stimulated PON activity in poor control group. OxLDL level was not statistically significant among the three groups however the PON to oxLDL ratio (PON/oxLDL) shows significantly higher in healthy control compared to poor control diabetic group. Conclusion: AREase activity was lower in T2 DM patients compared to healthy control and majority of subjects (Malay population) were AB phenotype. Poor control T2 DM group had lesser PON/oxLDL ratio when compared with healthy control and good control T2DM although PON and oxLDL levels not significant. Thus it could relate with the risk of complications in poor control T2 DM.